ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN KABUPATEN/KOTA DI PROVINSI BALI - Endrayani, Ni Ketut Eni; Urmila Dewi, Made Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
S ituation of deprivation due to limited capital owned, lack of knowledge and skills, low productivity, low income, the weak exchange rate of the poor yield and the limited opportunities to participate in development. This then lead to inequality in society. This study aimed to analyze the factors affecting the level of poverty district / city in the province of Bali. Data used in this research is secondary data. Location of research in the district / city in the province of Bali. Results of hypothesis testing is done with the path analysis showed that the inflation effect of reducing poverty through unemployment in the province of Bali. The level of education has no effect on poverty through unemployment in the province of Bali. Investment influential increasing poverty through unemployment in Bali province either directly or indirectly through intervening variables, namely unemployment.
Keywords: inflation, level of education, investment, unemployment, poverty